2004
DOI: 10.1007/s00439-003-1045-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the mutation spectra of Menkes disease and Wilson disease

Abstract: The genes for two copper-transporting ATPases, ATP7A and ATP7B, are defective in the heritable disorders of copper imbalance, Menkes disease (MNK) and Wilson disease (WND), respectively. A comparison of the two proteins shows extensive conservation in the signature domains, with amino acid identities outside of the conserved domains being limited. The mutation spectra of MNK and WND were compared to confirm and refine further regions critical for normal function. Mutations were found to be relatively widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 51 publications
1
27
1
Order By: Relevance
“…Two of these lie within transmembrane (Tm) domains 2 and 5, with scores of 0.21,and 0.07 respectively, and we consider them to be disease causing because of their positions within ATP7B. Changes in the copper 6 to Tm1 region have been found in ATP7A (Hsi and Cox, 2004) and may alter flexibility of the protein in this region, although SIFT scores for two mutations are 0.21 and 0.08. Mutations are not expected between copper binding domains 5 and 6 (p.Y532H) or within copper 6 (p.G591D), because of the redundancy of copper domains and the lack of mutations in ATP7A in this region (Hsi and Cox, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these lie within transmembrane (Tm) domains 2 and 5, with scores of 0.21,and 0.07 respectively, and we consider them to be disease causing because of their positions within ATP7B. Changes in the copper 6 to Tm1 region have been found in ATP7A (Hsi and Cox, 2004) and may alter flexibility of the protein in this region, although SIFT scores for two mutations are 0.21 and 0.08. Mutations are not expected between copper binding domains 5 and 6 (p.Y532H) or within copper 6 (p.G591D), because of the redundancy of copper domains and the lack of mutations in ATP7A in this region (Hsi and Cox, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the copper 6 to Tm1 region have been found in ATP7A (Hsi and Cox, 2004) and may alter flexibility of the protein in this region, although SIFT scores for two mutations are 0.21 and 0.08. Mutations are not expected between copper binding domains 5 and 6 (p.Y532H) or within copper 6 (p.G591D), because of the redundancy of copper domains and the lack of mutations in ATP7A in this region (Hsi and Cox, 2004). The change in hydrophobicity and replacement by histidine, a residue typically involved in copper binding (p.Y532H) and a SIFT score of 0 (p.G591D), make them acceptable as disease causing.…”
Section: Resultsmentioning
confidence: 99%
“…The long loop comprising residues 1114-1142 is not involved in ATP binding (Dmitriev et al, 2006) and there are no known Wilson's disease mutations in this region (Hsi & Cox, 2004), which implies that this region is not critical for enzyme function and that the core N-domain structure would not be altered by deletion of this loop. At the same time, the disordered state of this loop may have prevented successful crystallization of the full-length N-domain.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mutations of the human Cu ϩ -ATPases, ATP7A and ATP7B, leads to Menkes' and Wilson's disease, respectively (1,2). Similarly, the knockout of Arabidopsis thaliana Cu ϩ -ATPase genes produces significant, and in some cases lethal, physiological alterations (3,4).…”
mentioning
confidence: 99%
“…Biochemical studies supporting different aspects of this cycle have shown metal-dependent ATPase activity, metal transport capability, interaction of ATP with high and low affinity, phosphorylation of the invariant Asp in the DKTGT sequence, distinct E1P and E2P forms, and the typical inhibition by vanadate observed in all P-type ATPases (6, 10 -16). Cu ϩ -ATPases have eight transmembrane segments (TMs) 1 with a large cytoplasmic loop located between their sixth (H6) and seventh (H7) TMs and responsible for ATP hydrolysis (8,9,17,18) (Fig. 2).…”
mentioning
confidence: 99%